2015
DOI: 10.1179/1362171815y.0000000043
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and texture evolution of stationary shoulder friction stir welded Ti6Al4V alloy

Abstract: Microstructure evolution and texture evolution in the weld zones during stationary shoulder friction stir welding of Ti6Al4V alloy of 7 mm thickness have been investigated by optical microscopy and electron backscatter diffraction method. A unique method was developed to differentiate the heat affected zone (HAZ) and the thermomechanically affected zone (TMAZ). The weld zones are characterised by equiaxed structure in the base material (BM), bimodal structure in the HAZ, coarse lamellar structure in the TMAZ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…To improve the weldability and joint properties of FSW of titanium alloys, stationary shoulder FSW (SSFSW) was invented by TWI in 2004 to solve the problems of gradient temperature distribution, especially the surface overheating, along the thickness direction of the titanium joints due to its low thermal conductivity [19], and a relatively homogenous microstructure along the direction of plate thickness was reported by Russell et al and Wynne et al [20, 21] with excellent forming and good joint performance. Davies [22] and Jiang [23, 24] also observed the uniformed distributed microhardness along the plate thickness with varying welding parameters. SSFSW solves the problem of surface overheating, produces a much more uniform heat input imposed on the joint and improves the joint quality.…”
Section: Introductionmentioning
confidence: 98%
“…To improve the weldability and joint properties of FSW of titanium alloys, stationary shoulder FSW (SSFSW) was invented by TWI in 2004 to solve the problems of gradient temperature distribution, especially the surface overheating, along the thickness direction of the titanium joints due to its low thermal conductivity [19], and a relatively homogenous microstructure along the direction of plate thickness was reported by Russell et al and Wynne et al [20, 21] with excellent forming and good joint performance. Davies [22] and Jiang [23, 24] also observed the uniformed distributed microhardness along the plate thickness with varying welding parameters. SSFSW solves the problem of surface overheating, produces a much more uniform heat input imposed on the joint and improves the joint quality.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, stationary shoulder stir friction welding (SSFSW) was developed by The Welding Institute, UK, to eliminate the problem of uneven temperature distribution along the thickness direction. And it is urgent to quantify the thermomechanical conditions such as temperature and material flow to optimise welding parameters for SSFSW process [11].…”
Section: Introductionmentioning
confidence: 99%
“…The non-rotating shoulder slides along the weld line without rotation during the welding [6]. Initially, the tool with a non-rotating shoulder was developed for FSW of Ti alloys and later implemented for other metal systems such as aluminium [7]. Non-rotating shoulder tool has been reported to produce a defect-free weld joint of AA7075 at various speed parameters [8].…”
Section: Introductionmentioning
confidence: 99%
“…The material penetration occurs through the gap between rotating sub-shoulder and non-rotating shoulder. Previous studies [5][6][7][8][9][10][11][12][13] primarily reported the metallurgical and mechanical properties of the NRS-FSW joints. However, the corrosion behaviour of the NRSFSW joint of aluminium alloys has not been investigated to the best knowledge of the authors.…”
Section: Introductionmentioning
confidence: 99%